Long-term results of arthroscopic debridement and percutaneous pinning for chronic dynamic scapholunate instability. (June 2019) - Kim, Jin-Kak; Lee, Seung-Jin; Kang, Sae-Hyun; Park, Jun-Sik; Park, Jin; Kim, Gab-Lae
There are various treatments for chronic dynamic scapholunate instability and there is still much debate about the best method of treatment. We retrospectively analysed 42 patients who had been treated by arthroscopic debridement and percutaneous pinning for chronic dynamic scapholunate instability. All patients were clinically improved without radiographic changes after surgery and were still satisfied at a mean follow-up of 68 months. Arthroscopic debridement and percutaneous pinning may be a good option for treating chronic dynamic scapholunate instability. Level of evidence: IV